UGT440A1 Is Associated With Motility, Reproduction, and Pathogenicity of the Plant-Parasitic Nematode Bursaphelenchus xylophilus - Wang, Min; Du, Guicai; Fang, Junna; Wang, Linsong; Guo, Qunqun; Zhang, Tingting; Li, Ronggui (Frontiers in Plant Science, 2022)
Pine wilt disease (PWD) caused by Bursaphelenchus xylophilus (B. xylophilus) is considered a major threat to pine forests worldwide. Uridine diphosphate (UDP)-glycosyltransferases (UGTs) catalyse the conjugation of small lipophilic compounds with sugars and play crucial roles in the detoxification and homeostatic processes in all living organisms. We investigated the molecular characteristics and biological functions of the gene UGT440A1 that encodes UGTs in B. xylophilus. The mRNA fluorescence in situ hybridisation results indicated that UGT440A1 is expressed in all developmental stages of B. xylophilus, particularly in the head, intestine, and hypodermis of the second-stage of juveniles (J2), third-stage of juveniles (J3) and fourth-stage of juveniles (J4) females and in almost the whole body of J4 males and adults. Recombinant UGT440A1 was observed mainly in the inclusion bodies, and the enzyme activity assay revealed that UGT440A1 could catalyse the glycosylation reaction of two types of flavonols (kaempferol and quercetin). RNA interference (RNAi) of UGT440A1 suppressed motility, feeding, and reproduction of B. xylophilus. Furthermore, UGT440A1 knockdown caused a delay in the development of PWD symptoms in the pine seedlings inoculated with the nematodes. These results suggest that UGT440A1 is involved in the pathogenic process of B. xylophilus and the information may facilitate a better understanding of the molecular mechanism of PWD.